Performance study on s-CO2 power cycle with oxygen fired fuel of s-water gasification of coal. (1st November 2019) - Zhu, Zilong; Chen, Yaping; Wu, Jiafeng; Zheng, Shuxing; Zhao, Wenjuan
Highlights: A fuel-oxy s-CO2 power cycle combining s-water gasification of coal was investigated. Cycle system is simplified with higher turbine backpressure to eliminate compressors. Gasification heating is completed by turbine exhaust flow to improve the efficiency. The influences of key parameters on the cycle performance were investigated. Abstract: A novel supercritical CO2 power cycle with oxygen fired fuel of supercritical water gasification of coal is schemed and studied in this paper. The coal gasification syngas is combusted with pure O2 and the combustion products mix with the circulation CO2 forming CO2 dominant CO2 /H2 O mixture for power generation. By setting the backpressure of turbine at the saturated value of ambient temperature, the circulation CO2 can be pressurized only by pump without compressors. The turbine inlet temperature is set at 950–1000 °C for suitable turbine exhaust temperature for gasification heating. The turbine exhaust vapor is first led to heat the gasification process before releases heat in regenerators and condenser. The effect of key parameters on the cycle performance was investigated and the results show that the turbine inlet temperature, the condensation temperature and the ASU specific power consumption have significant effects on net efficiency of the cycle. Under the parameters of turbine inlet parameters of 25 MPa/1000 °C, condensation temperature of 25 °C and ASU specific power consumption of 0.245 kWh·kg −1 (O2 ), the net efficiency of the cycle achieves 47.3% with full CO2 capture.